Influence of storage time on stability of routine coagulation parameters (international normalised ratio, activated partial thromboplastin time and fibrinogen) at room temperature - Chen, Richard M; Wee, Yii Sen; Lucas, Rhonda (New Zealand journal of medical laboratory science, 2021)
Objectives: Extending the maximum acceptable specimen age for testing/retesting some routine coagulation parameters has many benefits (e.g., reagent evaluation, fibrinogen add-on for disseminated intravascular coagulation, or addressing sample delay during snow in Otago/Southland). This study assessed such possibility, where stability of international normalised ratio, activated partial thromboplastin time and Fibrinogen results were examined in relation to storage time. Methods: From each participating individual (50 total), four citrate tubes were collected. A baseline tube was centrifuged and tested for international normalised ratio, activated partial thromboplastin time and fibrinogen at time of arrival. The other three tubes were kept as whole blood. After 24, 48, and 72 hours respectively from time of collection, one tube was taken for centrifuging and tested for international normalised ratio, activated partial thromboplastin time, and fibrinogen. In addition, centrifuged tubes were retested for international normalised ratio and fibrinogen after 24, 48, and 72 hours respectively (centrifuged fibrinogen after 96 hours) from time of collection. All specimens were kept at room temperature. Results: The mean bias of international normalised ratio, activated partial thromboplastin time, and fibrinogen at after 24h, 48h, and 72h (centrifuged fibrinogen after 96h) were calculated and compared with specific allowable limits of performance. For both centrifuged and uncentrifuged specimens, international normalised ratio variations up to 72h all passed Royal College of Pathologists of Australasia allowable limits of performance (+-0.3); fibrinogen variations up to 72h (centrifuged fibrinogen up to 96h) all passed European Federation of Clinical Chemistry and Laboratory Medicine allowable limits of performance (+-10.7%). Activated partial thromboplastin time had a clear increasing trend, and all of its variations failed the European Federation of Clinical Chemistry and Laboratory Medicine allowable limits of performance (+-2.7%). Conclusion: Evidence supports extension of maximum acceptable age of uncentrifuged specimens for international normalised ratio and fibrinogen tests to 72h. Changing the maximum allowable age of activated partial thromboplastin time is not recommended. For centrifuged specimens, we can extend maximum acceptable age for international normalised ratio to 72h and fibrinogen to 96h.